Wavelength tune of InGaN based blue LEDs by changing indium percentage and operational voltage variables - KIYAK, İSMAİL (My University, 2022)
Blue light-emitting-diodes (LEDs) are special and different than the other LEDs due to their high-efficient lighting. They have large badgap energy. So gallium nitrides are mostly used during designing blue light. This application focus on the emission properties of a InGaN LED. The emission intensity, energy diagram, spectrum, and efficiency are calculated for an applied voltage. The indium and GaN composition in the blue LED can be varied to control the emission wavelength. In here, composition of InGaN and operational voltage values were varied to control wavelength. Effects of the different InGaN composition and different voltage values were given in results as comprehensively for 5 different simulations. This study is dissimilar than other wavelength studies due to used original parameter values and wavelength compared methods for many situations about InGaN percentage and voltage values. As a result of simulations, we can infer that the high In_x percentage in composition and high voltage makes wavelength gap of an blue LED larger
Keywords: Comsol; InGaN; LED; Voltage; Wavelengths